2001
DOI: 10.2527/2001.793568x
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin-induced cervical dilation and cervical manipulation in sheep: effects on laparoscopic artificial insemination.

Abstract: The difficulty of cervical penetration severely limits the use of transcervical AI (TAI) in sheep, and trauma from cervical manipulation (CM) may reduce fertility after TAI. We investigated the effects of cervical dilation using exogenous oxytocin (OT) to facilitate TAI and its effects on reproductive variables after laparoscopic AI (LAI). Estrus was synchronized by inserting pessaries impregnated with 6alpha-methyl-17alpha-hydroxyprogesterone acetate (60 mg) for 12 d. In Exp. 1, we determined whether OT and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 18 publications
0
31
0
Order By: Relevance
“…Although they found no detrimental effect of oxytocin on fertilisation rate, the transcervical technique per se appeared to reduce fertilisation rate. In contrast, Stellflug et al (2001) found no adverse effect of experimental cervical manipulation on fertility in laparoscopically inseminated ewes, but lambing rates were decreased by oxytocin-induced cervical dilation. Using a brass bulb tip to decrease cervical trauma and to guide the inseminating pipette, WulsterRadcliffe and Lewis (2002) found no adverse effect of transcervical insemination on fertility.…”
Section: Transcervical Inseminationmentioning
confidence: 52%
See 1 more Smart Citation
“…Although they found no detrimental effect of oxytocin on fertilisation rate, the transcervical technique per se appeared to reduce fertilisation rate. In contrast, Stellflug et al (2001) found no adverse effect of experimental cervical manipulation on fertility in laparoscopically inseminated ewes, but lambing rates were decreased by oxytocin-induced cervical dilation. Using a brass bulb tip to decrease cervical trauma and to guide the inseminating pipette, WulsterRadcliffe and Lewis (2002) found no adverse effect of transcervical insemination on fertility.…”
Section: Transcervical Inseminationmentioning
confidence: 52%
“…Such a conclusion is in keeping with the adverse effect on conception noted by King et al (2004) following systemic oxytocin administration before cervical insemination using frozen-thawed semen and the absence of a deleterious effect of the oxytocin on conception when the cervix was by-passed by laparoscopic intrauterine insemination. It is also in keeping with the data of Stellflug et al (2001), which imply that a combination of exogenous oxytocin and cervical manipulation accentuates the oxytocinmediated impairment of fertility following cervical insemination. Thus, King et al (2004) suggested that, when using oxytocin for enhancing cervical dilation and os cervix activity, it may be advantageous to replace a single relatively large bolus dose of oxytocin, which results in an extended period of elevated oxytocin concentrations, with a series of smaller doses that more closely mimic, in number, amplitude and duration, the pulses in plasma concentrations that occur during natural oestrus (Sheldrick and Flint, 1981;Wathes et al, 1986;Gilbert et al, 1991).…”
Section: Cervical Activitymentioning
confidence: 53%
“…Therefore, it is tempting to speculate that a secretion of OT altering the contractile rate of the uterus for a long period is detrimental to fertility in a number of species, including the ewe. For example, it has recently been shown that the administration of OT at the time of AI does not improve pregnancy rates, and tends to reduce fertility [36,40,45]. Furthermore, there is evidence that in an attempt to enhance sperm transport, such an OT treatment in the ewe considerably diminishes the number of spermatozoa recovered in the fallopian tubes after insemination [27].…”
Section: Discussionmentioning
confidence: 99%
“…Sayre and Lewis (1997) observed no undesirable effect of oxytocin on ovum fertilisation rate. Stellflug et al, (2001) show a negative effect of oxytocin but not of the transcervical insemination procedure. Fertilization rate decreases in the treatment of oxytocin-cervical manipulations.…”
Section: Oxytocinmentioning
confidence: 99%
“…The cervical manipulation seems to unfavorable an effect on fertility after AI, because the oxytocin treatment is not harmful. It likely to affect the sperm survival in the reproductive tract of sheep, or some issues of sperm capacitation (Stellflug et al, 2001). Perhaps, manipulation of the cervix may affect sperm transport within the reproductive tract, or a stressed cervix may produce a spermicidal compound (Hawk et al, 1981).…”
Section: Oxytocinmentioning
confidence: 99%